Glial cell line-derived neurotrophic factor inhibits mast-cell-like RBL-2H3 cells activation via Ca2+-mediated degranulation and Ca2+/CaMKⅡ/JNK pathway - Huang, Wei; Zeng, Li; Zhang, Li; Zhang, Xinxing; Xie, Qin (Frontiers in Pharmacology, 2025)
IntroductionMast cells are important component of the intestinal immune system, play a crucial role in the pathogenesis of inflammatory bowel disease. Glial cell line-derived neurotrophic factor (GDNF), as a multifunctional growth factor, has recently garnered attention for its role in the inhibition of mast cells activation. This study aims to explore the potential mechanisms by which GDNF inhibits mast cell activation.MethodsIn this study, RBL-2H3 cells were used as an in vitro cell model of mast cells, which were cultured and treated with various interventions prior to collection of cells and culture supernatants. IgE-mediated degranulation were evaluated through β-hexosaminidase release assays. Culture supernatants were analyzed for TNFα, IL-1β, and IL-6 secretion using ELISA. Key signaling molecules—GDNF family receptor α1 (GFRα1), receptor Tyrosine Kinase (RET), calcium/calmodulin-dependent protein kinase II (CaMKⅡ), total and phosphorylated c-Jun N-terminal kinase (JNK), and JNK isoforms—were quantified at mRNA and protein levels using Quantitative Real-time polymerase chain reaction and Western blot. Intracellular Ca2+ were monitored fluorometrically. Immunofluorescence and protein binding assays were used to confirm interactions between GDNF-GFRα1/RET complexes and CaMKⅡ-JNK associations.ResultsGDNF inhibited the degranulation and release of inflammatory cytokines in activated RBL-2H3 cells. The intracellular Ca2+ and the phosphorylation of JNK were reduced in activated RBL-2H3 cells after GDNF treatment. Immunofluorescence results demonstrated co-localization of GDNF with GFRα1 on RBL-2H3 cell membranes and CaMKII with JNK in the cytoplasm. There were interactions between GDNF and GFRα1/RET, as well as CaMK II and JNK. RET inhibitor eliminated this inhibitory effect of GDNF on RBL-2H3 cell degranulation and inflammatory factor release. Ca2+ chelator and CaMKⅡ RNAi had the same inhibitory effect on degranulation, release of inflammatory cytokines and phosphorylation of JNK. However, in their presence, GDNF had no additional inhibitory effect.ConclusionGDNF can decrease the intracellular concentration of Ca2+ in activated RBL-2H3 cells by attaching to GFLα1/RET receptors located on the membrane of RBL-2H3 cells, subsequently inhibiting Ca2+-mediated degranulation and the Ca2+/CaMKII/JNK pathway responsible for the release of inflammatory cytokines.